Receiving the agriculture information through mass media and interpersonal sources among the rural community - Hassan, Md. Salleh; Md. Yassin, Sulaiman; Mohamed Shaffril, Hayrol Azril; Othman, Mohd Shahwahid; Abu Samah, Bahaman; Abu Samah, Asnarulkhadi; Ramli, Siti Aisyah (Science Publications, 2011)
Problem statement: Developing agriculture by disseminating the right information to the right groups has proven to be an effective strategy. In Malaysia, there are a number of sources; either mass media or personal sources that disseminate the agriculture information. The rural community, a group which are highly related to agriculture certainly have a pivotal need for agriculture information. Besides the existence of numerous sources of agriculture information, do the rural community especially those who living along Pahang and Muar Rivers have received adequate agriculture information from the mass media and interpersonal sources? This study would provide the answer for the query. Approach: This is a quantitative study, where a developed questionnaire was employed to gain the data needed. Through a simple random sampling, 900 respondents were selected. The respondents selected were among the villagers that live along Pahang and Muar Rivers. Descriptive and inferential analyses were employed to achieve the objectives determined. Results: Based on the results, rural community living along Pahang and Muar rivers do receive agriculture information at a high level from television, newspaper, family members, friends and village leaders and village administration members. Further analysis employed has proven that there is significant difference in receiving the agriculture information from mass media and interpersonal sources among rural communities in the three districts studied. Conclusion/recommendation: It is recommended that brochures/pamphlets that contain information on the list of agriculture programs available on television, radio, newspaper and internet can be produced by the concern parties and distributed to the rural people. The concern parties in agricultural delivery system are recommended to employ the media that are pertinent in fulfilling rural community needs.